1992
DOI: 10.1017/s0014479700019876
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Light Interception and the Efficiency of Light Utilization by the Coconut Palm (Cocos nucifera)

Abstract: A mobile sampling method was used to measure the amount of photosynthetically active radiation (PAR) transmitted through the canopies of coconut palms in two long term field trials. PAR transmissions were measured at approximately monthly intervals for one year. Fractional interception of light was found to vary considerably between months, and to be associated with frond shedding caused by dry season water stress. Palms receiving potassium fertilizer intercepted more light and replaced leaf area lost during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Based on these measurements, Moss (1992) was able to demonstrate a close linear relationship between yield of copra (and the whole fruit) and cumulative light interception ( n = 6; r 2 = 90%). As the line(s) did not pass through the origin, this suggested that there was a minimum level of light interception below which no yield is produced.…”
Section: Crop Developmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on these measurements, Moss (1992) was able to demonstrate a close linear relationship between yield of copra (and the whole fruit) and cumulative light interception ( n = 6; r 2 = 90%). As the line(s) did not pass through the origin, this suggested that there was a minimum level of light interception below which no yield is produced.…”
Section: Crop Developmentmentioning
confidence: 98%
“…So although young palms in a plantation cover the ground, well older palms do not. Using a mobile sampling method in Thailand, Moss (1992) measured the amount of photosynthetically active radiation intercepted by the leaf canopy at monthly intervals throughout one year. Seasonal reductions in the amount of light intercepted were related to water stress, its most immediate effect being to increase the rate of frond shedding and to slow the production of new fronds.…”
Section: Stem and Leavesmentioning
confidence: 99%
“…These concepts have not been applied to the coconut palm (Cocos nucifera L.), though Moss (1992) studied the ratio of copra yield to canopy light interception, which is effectively the product of e and P. To estimate total dry matter production for coconut requires measurement of the dry weight of the nuts and also of vegetative dry matter production. The dry weight of copra, the main product, is routinely measured or estimated in the majority of coconut experiments.…”
Section: Introductionmentioning
confidence: 99%